Strain-induced specific orbital control in a Heusler alloy-based interfacial multiferroics - Jun Okabayashi; Takamasa Usami; Amran Mahfudh Yatmeidhy; Yuichi Murakami; Yu Shiratsuchi; Ryoichi Nakatani; Yoshihiro Gohda; Kohei Hamaya (NPG Asia Materials)
Abstract For the development of spintronic devices, the control of magnetization by a low electric field is necessary. The microscopic origin of manipulating spins relies on the control of orbital magnetic moments (m orb) by strain; this is essential for the high performance magnetoelectric (ME) effect. Herein, electric-field induced X-ray magnetic circular dichroism (XMCD) is used to determine the changes in m orb by piezoelectric strain and clarify the relationship between the strain and m orb in an interfacial multiferroics system with a significant ME effect; the system consists of the Heusler alloy Co2FeSi on a ferroelectric Pb(Mg1/3Nb2/3)O3-PbTiO3 substrate. Element-specific investigations of the orbital states by operando XMCD and the local environment via extended X-ray absorption fine structure (EXAFS) analysis show that the modulation of only the Fe sites in Co2FeSi primarily contributes to the giant ME effect. The density functional theory calculations corroborate this finding, and the growth of the high index (422) plane in Co2FeSi results in a giant ME effect. These findings elucidate the element-specific orbital control using reversible strain, called the ‘orbital elastic effect,’ and can provide guidelines for material designs with a giant ME effect.